COMMUNITY TOLERANCE: RELATIONSHIP OF MUSLIM MAJORITY AND CHRISTIAN MINORITY IN THE CONTEXT OF RELIGIOUS MODERATION IN PADANG PARIAMAN, WEST SUMATERA - Andri Ashadi; Ronal A Lukens-Bull; Seren Valentina; Makhsus Makhsus; Danil Folandra (Penamas, 2022)
Intolerance was often pinned on communal societies such as Indonesia because it uses a liberal-secular tolerance perspective which is identical to Western Christian society. If the perspective is shifted, for example using communal tolerance, the communal community will also practice the opposite, tolerance. This paper is intended to reveal and analyze how the Muslim community in the Nagari KH which is considered the majority practices tolerance on a community scale in the context of religious moderation towards the Christian minority in the Nagari. In addition, it also analyzes why the model's tolerance can occur. This research is qualitative research that relies on interview data from elements of the nagari government, penghulu, youth leaders, religious leaders and adherents of Islam and Christianity from both communities. The data is reinforced by document data including journals and research reports that are relevant to the research topic. The results show that community tolerance as a form of religious moderation has been practiced by the Muslim community of KH in the socio-economic and religious realms. In the socio-economic aspect, community tolerance appears in the form of openness to business, buying and selling and ownership of land and houses. While in the religious realm it is limited to individual and family worship at homes. The ambivalence of tolerance practiced by the Muslim community of KH is rooted in the ambivalence of Minangkabau culture on a macro level and the ambivalence of the geographical position of Nagari KH on a micro basis. Minangkabau cultural ambivalence collides and synthesizes matrilineal customs and matrilineal Islam. Meanwhile, the ambivalence of being a coastal area is at the same time bordering on darek. Both have given birth to an inclusive attitude towards immigrants in the socio-economic realm and exclusive when it comes to communal worship.